Land use land cover change and public perceptions differently affect black crowned crane (Balearica pavonina) conservation: Evidences from Jimma zone southwestern Ethiopia - Dessalegn Obsi Gemeda; Tekalign Abdisa Kerbe; Habte Wondime Gemechu (Environmental and Sustainability Indicators, 2023)
Land use land cover (LULC) change study can provide a scientific ground for species conservation. The present study aimed to analyze the effect of LULC change on Black Crowned Crane (Balearica pavonina), and public perception of species conservation. A Landsat 7 ETM +2000, and Landsat 8 OLI of 2020 were used to analyze the LULC change. Maximum likelihood supervised classification technique was employed to classify the LULC types. Besides geospatial technologies, 151 household heads, key informant interviews (n = 6) and field observation were conducted. Results showed that agricultural land was increased from 74.24% in 2000 to 81.66% in 2020. Settlement and grazing land cover classes show a slight increased. Agricultural expansions on the expense of forest, grassland and wetlands substantial affect the conservation of B. pavonina. Wetland ecosystem declined slightly from 0.69% in 2000 to 0.58% in 2020. The decline of wetland ecosystems significantly threats B. pavonina, as the species used for feeding, breeding, and roosting. A household survey showed that 93.4% perceived that environmental changes had a significantly impact on B. pavonina. About 44.4% of the respondents perceived that the population of B. pavonina declined, while about 25.8%, 25.2%, and 4.6% perceived increasing, no change, and don't know, respectively. About 53.6% and 27.8% of the respondents perceived that the species is currently vulnerable and endangered, respectively. This study provides a baseline data on the threat of B. pavonina conservation. Other threats to this species, namely climate change, predators, and poaching can be studied by other scholars.